Negative urgency and central adiposity in a community sample: Moderated mediation by depressive symptoms and eating behaviors. (December 2021) - Shell, Aubrey L.; Oglesby, Larissa T.; Um, Miji; Stewart, Jesse C.; Cyders, Melissa A.
Abstract: Negative urgency – acting rashly in response to negative emotions – is a risk factor for central adiposity. We examine whether the relationship between negative urgency and waist-to-height ratio (WHtR) is mediated by eating behaviors (emotional eating, external eating, and cognitive restraint) and moderated by depressive symptom severity, factors that could be targeted to reduce risk associated with negative urgency. Using baseline data from the Nathan Kline Institute-Rockland Sample ( N  = 872; mean age = 42.4 years, SD  = 15.3; 65% female; 27% non-White; mean body mass index = 27.9 kg/m 2, SD  = 5.9), we conducted a series of mediation and moderated mediation analyses controlling for age, sex, race, and socioeconomic status. Overall, there was a positive association between negative urgency and WHtR. Emotional eating ( ab  = 0.02, SE  = 0.003, 95% CI [0.02, 0.03]) and uncontrolled eating ( ab  = 0.008, SE  = 0.002, 95% CI [0.004, 0.01]) were partial mediators of the relationship between negative urgency and WHtR, while cognitive restraint was not. In a parallel mediation model, emotional eating remained significant, while uncontrolled eating did not. Depressive symptom severity moderated the indirect effect of negative urgency on WHtR through emotional eating ( b int  = −0.08, p  < .001) but not the direct effect of negative urgency on WHtR. Our results indicate that emotional eating is a viable potential mechanism explaining the relationship between negative urgency and WHtR, and the indirect effect of negative urgency on WHtR through emotional eating becomes stronger as depressive symptom severity decreases. Highlights: Emotional eating mediates negative urgency and waist-to-height ratio. This indirect effect becomes stronger as depressive symptom severity decreases. Cognitive restraint and uncontrolled eating are less important to this relationship.